Microstructure and tribological properties of epoxy composites modified by methyl silicone oil-loaded microcapsules and/or reinforced with potassium hexatitanate whiskers. (April 2020) - Mu, Bo; Li, Xin; Yang, Baoping; Cui, Jinfeng; Wang, Xia; Guo, Junhong; Bao, Xuemei; Chen, Li
Self-lubricating functional microcapsules using melamine-formaldehyde resin encapsulating methyl silicone oil as core materials were synthesized by in situ polymerization method. And they are further adopted as antifriction additive to improve the tribological properties of binary and ternary epoxy (EP) composites, which were fabricated by incorporating microcapsules and the potassium hexatitanate whiskers (PTWs) into the EP matrix. The tribological behaviors of the as-synthesized EP composites have been evaluated by means of a block-on-ring high-speed wear tester. The results demonstrated that the friction coefficient and wear rate of EP /microcapsules binary composites decreased with the increase of microcapsule concentration due to the self-lubricating effect of the core material. For the EP /microcapsules/PTWs ternary composites, not only the mechanical properties and thermal stability PTWs were improved, but also the friction reduction and antiwear effect of the ternary composite are further enhanced due to the synergistic effect of PTWs and microcapsules.